mdm-2 inhibits the G1 arrest and apoptosis functions of the p53 tumor suppressor protein. - Chen, J (1996)
The mdm-2 gene encodes a 90-kDa polypeptide that binds specifically to the p53 tumor suppressor protein. This physical interaction results in the inhibition of the transcriptional functions of p53 (J. Chen, J. Lin, and A. J. Levine, Mol. Med. 1:142-152, 1995, and J. Momand, G. P. Zambetti, D. C. Olson, D. George, and A. J. Levine, Cell 69:1237-1245, 1992). Experiments are described that demonstrate the ability of mdm-2 to abrogate both the p53-mediated cell cycle arrest and the apoptosis functions. In addition, the results presented here suggest that mdm-2 binding to p53 and the resultant inhibition of p53 transcription functions are critical for reversing p53-mediated cell cycle arrest. The N-terminal half or domain of the mdm-2 protein is sufficient to regulate these biological activities of p53, consistent with the possibility that the highly conserved central acidic region and the C-terminal putative zinc fingers of mdm-2 may encode other functions.